Unilateral carbon pricing and heterogeneous firms - Robin Sogalla (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Several empirical studies document the relevance of firm heterogeneity to assess the effect of trade and environmental policy. This paper develops a multi-country and -sector general equilibrium trade model with heterogeneous firms and analyzes the effect of domestic carbon pricing as well as carbon border adjustments. In the presence of heterogeneous firms, these unilateral carbon pricing tools affect the emission intensity both via within- and across-firm adjustments. I show that the across-firm reallocation of market shares can be quantified ex-ante using publicly available data on the share of exporting firms. Applying the model to EU climate policy, I find that emission reductions arise mainly through a lower emission intensity of production within firms, while the reallocation channel is negligible. Scale economies aggravate the output loss of emission-intensive manufacturing and the reduction of real income due to more stringent climate policy, but increase the effectiveness of border adjustments to counter carbon leakage. The selection of heterogeneous plays a more limited role for aggregate effects.
Keywords: F12; F13; F18; Q54; Q56; 330; International trade; Firm heterogeneity; Unilateral climate policy; Carbon Border Adjustment; GHG emissions